PARENTAL PSYCHOSOCIAL ATTITUDES AND OPINIONS ON THE USE OF PSYCHOTROPIC MEDICATION IN MENTAL DISORDERS OF CHILDHOOD: Psychotropic Medication in Mental Disorders of Childhood - Abid, Dr Hafsa; Hamdani, Syed Usman; Shafique, Fakhira; Aadil, Muhammad (Pakistan Armed Forces Medical Journal, 2018)
Objective: To assess parental practices and attitude regarding administration of psychotropic agents in theirchildren suffering from psychiatric disorders.Study Design: Cross sectional descriptive study.Place and Duration of Study: Psychiatry Out-Patient Department (OPD) Mayo Hospital conducted over a span of6 months, from 15 Apr to 15 Oct 2017.Material and Methods: Ninety three individuals were included in the study through non-probability purposivesampling. Informed consent was taken from the parents. A closed ended questionnaire was designed to carry outa targeted survey which was focused on the knowledge and practices followed by parents during their firstcontact in an outpatient department. Parents were asked whether they believe that psychotropic drugs areeffective in the treatment of mental disorders.Results: Results are based on ninety three responders who participated in answering the questionnaire. Eightyturned out and submitted the questionnaire for result compilation and analysis. Participants ranged from 19 to 65years. Males outnumbered female’s patients during the study period by approx, 20%. The study indicated thattwo third of the patients had family history of mental illness. Common diagnosis included epilepsy, behavioral/conversion disorders and mental retardation. One thought-provoking finding among parents was thatpsychotropic drugs lead to certain side effects and somehow effects which may causes biological abnormalitiesresulting into several medical diseases. Others had a belief that these drugs are addictive and may cause vitalorgans failure.Conclusion: Mostly parents were of the opinion that are of psychotropic drugs lead to certain side effects andsomehow effects brain which may cause biological abnormalities resulting into several medical diseases.